avian Z-linked gene DMRT1 is required for male sex determination in the chicken - Smith, Craig A; Roeszler, Kelly N; Ohnesorg, Thomas; Cummins, David M; Farlie, Peter G; Doran, Timothy J; Sinclair, Andrew H (Nature (London), 2009)
Sex in birds is chromosomally based, as in mammals, but the sex chromosomes are different and the mechanism of avian sex determination has been a long-standing mystery. In the chicken and all other birds, the homogametic sex is male (ZZ) and the heterogametic sex is female (ZW). Two hypotheses have been proposed for the mechanism of avian sex determination. The W (female) chromosome may carry a dominant-acting ovary determinant. Alternatively, the dosage of a Z-linked gene may mediate sex determination, two doses being required for male development (ZZ). A strong candidate avian sex-determinant under the dosage hypothesis is the conserved Z-linked gene, DMRT1 (doublesex and mab-3-related transcription factor 1). Here we used RNA interference (RNAi) to knock down DMRT1 in early chicken embryos. Reduction of DMRT1 protein expression in ovo leads to feminization of the embryonic gonads in genetically male (ZZ) embryos. Affected males show partial sex reversal, characterized by feminization of the gonads. The feminized left gonad shows female-like histology, disorganized testis cords and a decline in the testicular marker, SOX9. The ovarian marker, aromatase, is ectopically activated. The feminized right gonad shows a more variable loss of DMRT1 and ectopic aromatase activation, suggesting differential sensitivity to DMRT1 between left and right gonads. Germ cells also show a female pattern of distribution in the feminized male gonads. These results indicate that DMRT1 is required for testis determination in the chicken. Our data support the Z dosage hypothesis for avian sex determination.